Peningkatan Kemampuan Menulis Teks Deskripsi Dengan Model Inkuiri Pada Siswa Kelas VII - Sidi Hermanto; Farida Ariyani; Muhammad Fuad (Universitas Lampung, 2019)
This research is made based on the observation of low ability in writing descriptive text of the VII grade students of the Junior High School of Tanggamus 2. This research used Classroom Action Research Method that was conducted in three cycles. Each cycle was done in two meetings, the firs meeting was to collect the data and arrange the writing framework and contiued by writing descriptive text at school. The second meeting was to evaluate the implementation of inquiry model covered the evaluation of learning process and the results of students works. The average score of writing descriptive text in pre-cycle in the VII grade was 50,62 and it was categorized minus. Meanwhile in the cycle I, it had an increase with the average score was 62,65 and it was categorized enough. In the cycle II, the average score was 71,09 and it was categorized good and in the cycle III, the average score was 84,84 and it was categorized very good.Penelitian ini menggunakan model tindakan kelas yang dilakukan dalam tiga siklus. Setiap siklus dilaksanakan dalam dua kali pertemuan, yaitu pelaksanaan model inkuiri untuk mengumpulkan data dan menyusun kerangka penulisan, dilanjutkan dengan tahap penulisan teks deskripsi di sekolah, penilaian terhadap pelaksanaan model inkuiri meliputi penilaian proses pembelajaran dan hasil kerja siswa. Skor rata-rata kemampuan menulis teks deskripsi pada prasiklus di kelas VII 50,62 dengan kategori kurang, sedangkan pada siklus I mengalami peningkatan dengan skor rata-rata adalah 62,65 dengan kategori cukup, pada siklus II rata-rata skor adalah 71,09 dengan kategori baik, dan pada siklus III rata-rata skor adalah 84,84 dengan kategori baik sekali. Kata kunci: model inkuiri, kemampuan menulis , teks deskripi